The Path to Persistence: How Conscientiousness and Social Integration Shape Academic Resilience in Higher Education - Kipuru, Moris Matembu; Kibanja, Grace M.; Matagi, Leon (East African Journal of Education Studies, 2024)
Research on academic persistence is foundational to higher education studies, as it directly impacts student success, retention, and graduation rates. Of the many factors influencing these outcomes, personality traits—especially conscientiousness—and social integration are particularly significant. This study examined the role of conscientiousness and social integration in promoting academic persistence among undergraduate students at Makerere University. Guided by a post-positivist perspective, the research employed a sequential explanatory mixed-methods design, prioritizing quantitative data to assess relationships between conscientiousness, social integration, and academic resilience, followed by qualitative interviews to provide deeper insights. A sample of 754 final-year students was surveyed, with follow-up interviews conducted with 14 participants selected through purposive sampling. Quantitative findings revealed significant positive correlations between conscientiousness, social integration, and academic persistence, with conscientiousness emerging as a strong predictor of persistence (ρ = .261, p < .01). Additionally, findings showed that social integration significantly mediates the relationship between conscientiousness and academic persistence (b=.15, p=.22). Qualitative data provided further understanding of these results, illustrating how traits such as diligence and organization, alongside supportive peer and faculty interactions, foster a sense of belonging and commitment to academic goals. The study concludes that fostering conscientious behaviours and social connectedness within university environments can enhance students' academic persistence. Recommendations include institutional policies that encourage peer integration, mentorship programs, and support for personality development. These findings contribute to the literature on academic persistence by highlighting the critical interplay between personality and social factors in students' success and by offering practical strategies to support student retention and achievement